An Innovative Clinic-Based Intervention to Improve Adolescent Access to Sexual and Mental Health Services: The Total Teen Program - Whitney Garney; Gan Han; Christi Esquivel; Kristen Garcia; Kobi V. Ajayi; Kelly Wilson (Journal of Primary Care & Community Health)
Objective: Adolescents encounter numerous healthcare access barriers, leading to poor health outcomes. Researchers developed the Total Teen (TT) program to improve access to sexual and reproductive health (SRH) and mental health (MH) services in settings providing adolescents and young adults (12-25) health services. This pilot study assessed the TT’s impact on care across three settings: school-based health clinics, a federally qualified health center, and an adolescent health clinic for 12 weeks. Methods: Sociodemographic data, including age, race/ethnicity, gender, and insurance status, were collected. MH was assessed using patient health questionnaire (PHQ)-9 and generalized anxiety disorder (GAD)-2 scales, and sexual health was evaluated based on CDC guidelines and additional evidence-based questions. One-on-one time, confidential consultations, SRH and MH micro visits, and referrals measured access. Descriptive statistics, Pearson Chi-square tests, and Kruskal–Wallis tests compared site outcomes, while logistic regression models adjusted for age, gender, race, and site. Results: Four hundred and fifty-one participated in the TT program across the three sites. Concerning micro visits and referrals, being male was associated with lower depression rates ( P  = .0003) and generalized anxiety disorder ( P  = .0099). Being males also predicted micro visit receipt ( P  = .0199). Concerning SRH micro visits, higher sexual behavior scores ( P  < .0001) were significantly associated with a greater likelihood of utilizing SRH micro visits. Conclusions: Results indicate that TT improves access to SRH and MH services and referrals for at-risk adolescents. Findings underscore the importance of integrating SRH and MH services into routine adolescent care and involving health organizations and providers as key stakeholders in enhancing preventive healthcare access.